A Systematic Review of Education-Job Market Alignment and Labour Dynamics in Nepal - Khanal, Ashish; Rayamajhi, Hari Bahadur; Chaudhary, Jairam; Keshari, Kriti; Gautam, Kshitiz; Sharma, Mahesh; Pandey, Namuna; Shrestha, Piyush Lal; Dahal, Asmita; Giri, Suja (Journal of Multidisciplinary Research Advancements, 2026)
This systematic review examines the alignment between Nepal’s education system and its labour market dynamics, highlighting a profound and persistent disconnect that shapes the country’s employment landscape. Through an analysis of 37 studies published between 2015 and 2025, the review identifies outdated curricula, insufficient industry-academia collaboration, and a cultural devaluation of vocational skills as key drivers of the mismatch. This misalignment produces graduates ill-equipped for market needs, fueling high youth underemployment and swelling the informal sector, which accounts for over 60% of employment. Consequently, international labour migration has become a default livelihood strategy, with remittances nearing 30% of GDP—a dependency that perpetuates domestic job scarcity and stifles productive investment. The review also highlights inequitable access to decent work, with persistent caste- and disability-based discrimination exacerbating labour market fragmentation. We conclude that isolated policy measures are insufficient; breaking this cycle requires a coordinated national strategy integrating educational reform, industrial policy, and inclusive social interventions to foster a resilient, equitable, and productive labour ecosystem in Nepal.